Comparison of Enterobius vermicularis Infection Rates among Schoolchildren in Tocra and Al Marj, Libya - Eman EL Frragani; Amal AL-Mayar; Heba Idris; Reem Faraj; Suha Muftah (AlQalam Journal of Medical and Applied Sciences, 2026)
Enterobius vermicularis infection remains a common intestinal parasitic disease among schoolchildren worldwide, yet it is often underestimated in public health programs. This study investigated the prevalence and distribution of E. vermicularis among 131 schoolchildren in Al Marj and Tocar cities, Libya. Data were analyzed by age, gender, and geographic location, and statistical tests were applied to assess associations. The overall prevalence was 69.5%, with 91 children testing positive and 40 negatives. Infection rates were slightly higher among females (57.1%) compared to males (42.9%), though the difference was not statistically significant (p = 0.820). Age distribution showed the highest prevalence among children aged 5–15 years, while those ≥15 years had lower rates, but again without significant association (p = 0.951). Geographic comparison revealed nearly equal infection rates between Al Marj and Tocar (p = 0.954). These findings confirm that E. vermicularis infection is widespread across demographic groups and highlight the need for integrated school-based interventions, including routine screening, hygiene education, and incorporation of pinworm control into broader deworming programs.